APPLICATION OF BLOOM'S TAXONOMY FOR DEVELOPING EDUCATIONAL TASKS IN PROGRAMMING (Web of Technology: Multidimensional Research Journal, 2024)
This article explores the application of Bloom's Taxonomy in designing educational tasks for programming courses. By systematically progressing through the cognitive levels of the taxonomy, educators can enhance the learning experience, encouraging students to move beyond rote memorization toward critical thinking and creativity. The approach fosters a structured pathway for developing programming skills, aligning tasks with the cognitive needs of learners. This method is particularly valuable in higher education contexts, where the cultivation of advanced problem-solving skills and innovative thinking is essential.